Refusal of COVID-19 booster vaccination among people living in remote tourism area, Samosir, Indonesia - Sitompul, Jos Iswadi; Anak Agung Sagung Sawitri; Dyah Pradnyaparamita Duarsa (Universitas Udayana, 2023)
Background and purpose: Samosir Island is a tourist area located in the middle of Toba Lake, Sumatra. It was reported that the coverage of COVID-19 booster vaccination had not reached the national target. This study aims to determine factors associated with the refusal of the COVID-19 booster vaccination. Methods: A community-based survey was conducted in the Sitiotio Sub-district of Samosir, from January to March 2023. Four out of eight villages were selected to represent the farthest and closer area. A multistage systematic random sampling was applied to select 156 out of 2073 households (HH). We interviewed 376 respondents to explore sociodemographic, experience of side effects of previous COVID-19 vaccination, comorbidities, family support, information, knowledge and perceptions. Booster vaccination status was determined through p-Care and immunization card. Descriptive, simple and multiple logistic regression were conducted. Results: About 32.4% of respondents refused the COVID-19 booster for fear of vaccine side effects (95.5%), had been vaccinated against COVID-19 (91.8%), and believed that the COVID-19 virus was gone (66.4%). The refusal of boosters was higher for those with low education, experienced side effects, have comorbidities, no family support and insufficient information, had poor knowledge and perception about COVID-19 vaccinations. Lack of trust of COVID-19 vaccine (AOR=2.31, 95%CI: 1.05-5.07), high perceived barriers (AOR=4.75, 95%CI: 1.96-11.49) and low self-efficacy (AOR=4.94, 95%CI: 1.44-16.98), less family support (AOR=6.34, 95%CI: 1.89-21.26) and poor knowledge (AOR=7.74, 95%CI: 1.74-34.02) significantly associated with COVID-19 booster vaccination refusal. Conclusion: Poor knowledge and perception of the COVID-19 vaccine and lack of family support increase refusal of the COVID-19 booster. Continuous evidence-based health promotion and family involvement can be carried out to increase public trust.